Perturbation of metabolic pathways mediates the association of air pollutants with asthma and cardiovascular diseases. (October 2018) - Jeong, Ayoung; Fiorito, Giovanni; Keski-Rahkonen, Pekka; Imboden, Medea; Kiss, Agneta; Robinot, Nivonirina; Gmuender, Hans; Vlaanderen, Jelle; Vermeulen, Roel; Kyrtopoulos, Soterios; Herceg, Zdenko; Ghantous, Akram; et al.
Abstract: Background: Epidemiologic evidence indicates common risk factors, including air pollution exposure, for respiratory and cardiovascular diseases, suggesting the involvement of common altered molecular pathways. Objectives: The goal was to find intermediate metabolites or metabolic pathways that could be associated with both air pollutants and health outcomes ("meeting-in-the-middle"), thus shedding light on mechanisms and reinforcing causality. Methods: We applied a statistical approach named 'meet-in-the-middle' to untargeted metabolomics in two independent case-control studies nested in cohorts on adult-onset asthma (AOA) and cardio-cerebrovascular diseases (CCVD). We compared the results to identify both common and disease-specific altered metabolic pathways. Results: A novel finding was a strong association of AOA with ultrafine particles (UFP; odds ratio 1.80 [1.26, 2.55] per increase by 5000 particles/cm 3 ). Further, we have identified several metabolic pathways that potentially mediate the effect of air pollution on health outcomes. Among those, perturbation of Linoleate metabolism pathway was associated with air pollution exposure, AOA and CCVD. Conclusions: Our results suggest common pathway perturbations may occur as a consequence of chronic exposure to air pollution leading to increased risk for both AOA and CCVD. Highlights: Strong association of long-term ultrafine particle exposure with adult-onset asthma Linoleate metabolism and carnitine shuttle as "meeting-in-the-middle" pathways. Metabolic pathways mediate the air pollution effects on health outcomes.